Thermodynamic Analysis of Beam down Solar Gas Turbine Power Plant equipped with Concentrating Receiver System. Issue 3 (September 2016) - Azharuddin,; Santarelli, Massimo
Abstract: Thermodynamic analysis of a closed cycle, solar powered Brayton gas turbine power plant with Concentrating Receiver system has been studied. A Brayton cycle is simpler than a Rankine cycle and has an advantage where the water is scarce. With the normal Brayton cycle a Concentrating Receiver System has been analysed which has a dependence on field density and optical system. This study presents a method of optimization of design parameter, such as the receiver working temperature and the heliostats density. This method aims at maximizing the overall efficiency of the three major subsystem that constitute the entire plant, namely, the heliostat field and the tower, the receiver and the power block. The results of the optimization process are shown and analysed.